Stability Indices and Micro-component Assessment of African Oil Bean Seed Oil Blended with Refined Palm - Onwuzuruike, Uzochukwu Anselm; Uluocha, Maduabuchi Daniel; Okwunodulu, Innocent N.; Eni, Agwo Obinna; Edima-Nyah, A. Peter; Blessing, Obasi Chidinma (PUI BiGME Universitas Jambi, 2026)
This study assessed the stability indices and micronutrient composition of African oil bean (Pentaclethra macrophylla) seed oil blended with refined palm olein (RPO). Edible oil was extracted from African oil bean seeds and blended with refined palm olein in varying proportions. The blended oils were subjected to stability studies for 12 days using an accelerated method (Schaal’s oven test), and the progression of oxidation was evaluated by determining the stability indices and micro-component content of the oil samples. The data generated were analyzed using one-way ANOVA, and mean separation was performed using Duncan’s multiple range test at a 95% confidence level. The results revealed significant differences (p < 0.05) across all measured parameters among the different oil samples. Oil yield determination showed that African oil bean seeds have a high oil content of 43.21%. The stability indices were affected during storage. The findings indicated that blended oils with a higher proportion of refined palm olein exhibited lower increases in peroxide value, free fatty acid value, and thiobarbituric acid value compared to pure African oil bean seed oil and blends with a higher proportion of African oil bean seed oil. The iodine values (IVs) of the oils decreased during storage, indicating depletion of double bonds. Specifically, AB100 decreased from 118.48 to 87.41 g I₂/100 g, RPO100 from 88.04 to 78.32 g I₂/100 g, RPO15:AB85 from 114.16 to 92.74 g I₂/100 g, RPO30:AB70 from 110.57 to 95.21 g I₂/100 g, and RPO50:AB50 from 102.20 to 94.14 g I₂/100 g. Vitamin E and beta-carotene contents decreased with accelerated storage; however, increasing the proportion of refined palm olein improved their retention. In conclusion, blending African oil bean seed oil with refined palm olein enhances its oxidative stability, with the highest stability observed in the 50:50 oil blend.